2016
DOI: 10.1136/bmjopen-2015-009928
|View full text |Cite
|
Sign up to set email alerts
|

Assessing herd immunity against rubella in Japan: a retrospective seroepidemiological analysis of age-dependent transmission dynamics

Abstract: ObjectiveWe aimed to epidemiologically assess rubella herd immunity as a function of time, age and gender in Japan, with reference to the recent 2012–2014 rubella epidemic.DesignThis study is a retrospective seroepidemiological analysis.Main outcome measuresThe susceptible fraction of the population was examined as a function of age and time. The age at infection was assessed using reported case data.ResultsWhereas 30 years ago rubella cases were seen only among children, the median (25–75th centiles) age of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Japan experienced a nationwide rubella epidemic from 2012 to 2013, which involved many infections among adults with a total of 45 reported CRS cases. While the country has clearly been on its way to achieve sufficient herd immunity to prevent any additional major epidemics, a seroepidemiological analysis of rubella revealed a “pocket” of susceptible individuals among males aged 30–49 years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Japan experienced a nationwide rubella epidemic from 2012 to 2013, which involved many infections among adults with a total of 45 reported CRS cases. While the country has clearly been on its way to achieve sufficient herd immunity to prevent any additional major epidemics, a seroepidemiological analysis of rubella revealed a “pocket” of susceptible individuals among males aged 30–49 years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The metapopulation epidemic model is a suitable tool to capture spatiotemporal dynamics over discrete patches, which are in line with the actual spatial distribution of a total of 47 prefectures in Japan [ 9 ]. Given that a substantial fraction of adults remains susceptible in the present day population in Japan [ 2 ], it is essential to explore possible vaccination strategies. The present study aimed to capture the spatiotemporal patterns of rubella using a parsimonious metapopulation epidemic model and examine the potential usefulness of a vaccination program that focuses on spatial heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Sadly, the history of vaccine crisis repeats itself in Japan. According to the previous studies, 3,6 the presence of disease-susceptible pockets was observed among the Japanese population, as shown in Fig. 1 .…”
Section: Japan's Failure To Provide Hpv Vaccines For Young Femalesmentioning
confidence: 52%
“…As a result, there are susceptible pockets among female birth cohorts 1989–1993, with seropositive proportions of 78.3%. 3 …”
Section: Rubella Epidemic In Japanmentioning
confidence: 99%
“…[9][10][11] and in other WHO regions. [12][13][14] When planning RCV introduction, serosurveys provide insight into the population subgroups that should be targeted for vaccination and provide data for modeling rubella transmission dynamics [15][16][17] including estimation of the burden of congenital rubella syndrome (CRS). Individuals of reproductive age are of particular interest since susceptibility to rubella in this age group has a direct impact on occurrence of CRS, which is the main target of the RCV.…”
Section: Introductionmentioning
confidence: 99%